Association between cardiac dysfunction and late gadolinium enhancement confined to the LV intramural region in patients with hypertrophic cardiomyopathy - Zhi Yang; Feng-you Yao; Yi-tian Long; Xue Meng; Liang-chao Gao; Yi You; Miao Wen; Shu-yue Pan (Annals of Medicine)
Aim/Introduction There are two major distributions of late gadolinium enhancement (LGE) in the context of hypertrophic cardiomyopathy (HCM): intramural LGE and LGE at right ventricular insertion points (RVIPs). However, the clinical significance of intramural LGE has not been well established.Materials and methods A total of 117 consecutive patients with HCM (61 male; median age, 58.8 years) confirmed by cardiovascular magnetic resonance (CMR) were enrolled, and classified into three groups: (1) no LGE (n = 48), (2) intramural LGE (n = 49), and (3) RVIP LGE (n = 20).Results Intramural LGE was detected in 41% of patients with HCM. HCM patients with intramural LGE had greater left ventricular (LV) wall thickness (LVWT) and greater LV mass than those without LGE (all p < 0.05). Furthermore, HCM patients with intramural LGE had a more depressed LV ejection fraction (LVEF) and more impaired global radial strain (GRS), global circumferential strain (GCS), and global longitudinal strain (GLS) than did those with RVIP LGE and those without LGE (all p < 0.05). Multivariate logistic regression analysis revealed that young age and severely thickened LVWT were associated with intramural LGE in patients with HCM (all p < 0.05). Furthermore, negative correlations were observed between intramural LGE and GRS, GCS, and GLS (all p < 0.001).Conclusions Intramural LGE is associated with more severe HCM phenotypes, including a greater LVWT, LV mass and extent of LGE; a reduced LVEF; and impaired myocardial strain. These findings indicate that intramural LGE may be a noninvasive biomarker for risk stratification in patients with HCM.